Characteristics Associated with Reliability in Reporting of Contraceptive Use: Assessing the Reliability of the Contraceptive Calendar in Seven Countries. Issue 1 (30th January 2023) - Anglewicz, Philip; Sarnak, Dana; Gemmill, Alison; Becker, Stan
Abstract: Although the reproductive calendar is the primary tool for measuring contraceptive dynamics in low‐income settings, the reliability of calendar data has seldom been evaluated, primarily due to the lack of longitudinal panel data. In this research, we evaluated the reproductive calendar using data from the Performance Monitoring for Action Project. We used population‐based longitudinal data from nine settings in seven countries: Burkina Faso, Nigeria (Kano and Lagos States), Democratic Republic of Congo (Kinshasa and Kongo Central Provinces), Kenya, Uganda, Cote d'Ivoire, and India. To evaluate reliability, we compared the baseline cross‐sectional report of contraceptive use (overall and by contraceptive method), nonuse, or pregnancy with the retrospective reproductive calendar entry for the corresponding month, measured at follow‐up. We use multivariable regressions to identify characteristics associated with reliability or reporting. Overall, we find that the reliability of the calendar is in the "moderate/substantial" range for nearly all geographies and tests (Kappa statistics between 0.58 and 0.81). Measures of the complexity of the calendar (number of contraceptive use episodes, using the long‐acting method at baseline) are associated with reliability. We also find that women who were using contraception without their partners/husband's knowledge (i.e., covertly) were less likely to report reliably in several countries.